Allopatric diversification, multiple habitat shifts, and hybridization in the evolution of Pericallis (Asteraceae), a Macaronesian endemic genus1. Issue 4 (1st April 2014) - Jones, Katy E.; Reyes‐Betancort, J. Alfredo; Hiscock, Simon J.; Carine, Mark A.
Abstract : Premise of the study: Geographic isolation, habitat shifts, and hybridization have contributed to the diversification of oceanic island floras. We investigated the contribution of these processes to the diversification of Pericallis, a genus endemic to Macaronesia. Methods: Data from the chloroplast psaI‐acc D and trn V‐ ndh C regions and the nuclear ribosomal internal transcribed spacer region (ITS) were sampled for multiple accessions of all taxa and used to establish phylogenetic hypotheses. Habitat preferences were optimized to investigate habitat shifts, and divergence times were estimated. Species nonmonophyly was investigated using Bayes factors. Key results: Much of the diversification in Pericallis has occurred recently, within the past 1.7 Ma. Three habitat shifts have occurred in the evolution of the genus. However, geographic isolation has played a greater role in its diversification. Novel allopatric patterns were revealed within some species, highlighting the significance of geographic isolation in the evolution of Pericallis . One species ( P. appendiculata ) that resolved as monophyletic in the ITS analysis was polyphyletic in the chloroplast analysis. Bayes factors provide strong support for the nonmonophyly of P. appendiculata haplotypes, and their phylogenetic placement suggests that ancient hybridization is responsible for the haplotype diversity observed. Conclusions: Multiple markers and extensive sampling provided new insights into the evolution of Pericallis . In contrast to previous studies, our results reveal a more significant role for allopatry than habitat shifts and new evidence for ancient hybridization in the evolution of Pericallis . Our study highlights the power of broad taxon sampling for unraveling diversity patterns and processes within oceanic island radiations.